Characteristics, seasonality, and trend of hospitalizations for Kawasaki disease in children from Peru, 2015-2019 - Atamari-Anahui, Noé (2023)
Introduction: There are limited epidemiological reports of Kawasaki disease (KD) in Latin America. Objective: To describe the characteristics, seasonality, and trend of hospitalizations for KD in children. Methods: Descriptive study of secondary analysis was performed with data on hospitalizations due to KD from healthcare institutions from Peru, 2015-2019. Results: Two hundred ninety-seven hospitalizations were registered. 59.9% were male. 82.2% were under five years old, and 16.2% were under one year old. The departments with more hospitalizations were Lima (202 cases), Lambayeque (21 cases), and Piura (17 cases). The seasons of the year with more hospitalizations were winter and spring. The incidence of KD increased from 0.52 to 2.28 cases per 100,000 children under five years old between 2015 and 2019. Conclusions: There was an increase in hospitalizations due to KD, more frequent in children under five years of age and males, and it occurred in all seasons.